Simultaneous synthesis and rapid consolidation of a nanocrystalline Mg0.6Al0.8Ti1.6O5 by high-frequency induction heating and its mechanical properties - Shon, In-Jin; Du, Song-Lee; Kang, Hyun-Su; Doh, Jung-Mann; Yoon, Jin-Kook (PERGAMON-ELSEVIER SCIENCE LTD, 2014)
A single-step synthesis and consolidation of nanostructured Mg0.6Al0.8Ti1.6O5 was achieved by highfrequency induction heating using the stoichometric mixture of MgO, Al2O3 and TiO2 powders. Before sintering, the powder mixture was high-energy ball milled for 10 h. From the milled powder mixture, a highly dense nanostructured Mg0.6Al0.8Ti1.6O5 compound could be obtained within one minute under the simultaneous application of 80 MPa pressure and an induced current. The advantage of this process is that it allows an instant densification to the near theoretical density while sustaining the nanosized microstructure of raw powders. The sintering behavior, microstructure and mechanical properties of Mg0.6Al0.8Ti1.6O5 were evaluated. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: FABRICATION; COMPOSITE